Предмет: Алгебра,
автор: nurya07
(-3xy^2)^3*2x^3y
(-3a^-2/b)^-3*9a^-5/b^2
Ответы
Автор ответа:
0
Пример 1
1) ( - 3XY^2) ^ 3 = ( - 27X^3Y^6 )
2) ( - 27 X^3Y^6) * 2X^3Y = ( - 54 X^6 Y^7 )
Ответ ( - 54 X^6 Y^7 )
-------------------------------------------------
Пример 2
1) (- 3A^(-2) / B) ^ -3 = ( A^6B^3) / - 27
2) 9A^-5 / B^2 = 9 / A^5B^2
3) (A^6B^3 / - 27 ) * ( 9 / A^5B^2) = AB / - 3 = - 1/3AB
Ответ - 1/3AB
1) ( - 3XY^2) ^ 3 = ( - 27X^3Y^6 )
2) ( - 27 X^3Y^6) * 2X^3Y = ( - 54 X^6 Y^7 )
Ответ ( - 54 X^6 Y^7 )
-------------------------------------------------
Пример 2
1) (- 3A^(-2) / B) ^ -3 = ( A^6B^3) / - 27
2) 9A^-5 / B^2 = 9 / A^5B^2
3) (A^6B^3 / - 27 ) * ( 9 / A^5B^2) = AB / - 3 = - 1/3AB
Ответ - 1/3AB
Похожие вопросы
Предмет: География,
автор: visbsbsvs
Предмет: Русский язык,
автор: fddnsu
Предмет: Русский язык,
автор: vasuninamarina76
Предмет: Математика,
автор: malvinademon
Предмет: Математика,
автор: malvinademon